2017
DOI: 10.1007/s00383-017-4078-3
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Morgagni diaphragmatic hernia: a descriptive study

Abstract: In this series, congenital MH appears to have a male predominance, frequently presents with pulmonary symptoms, and has excellent outcomes regardless of operative approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…laparoscopic repairs in infant as small as one month old have been successfully performed by our group and reported by others [17,27], suggesting appropriate patient selection is the key to success. Traditionally in adult practice when open repair was performed for MH, both thoracotomy and laparotomy had produced equal results [6,50].…”
Section: Accepted Manuscriptmentioning
confidence: 53%
See 1 more Smart Citation
“…laparoscopic repairs in infant as small as one month old have been successfully performed by our group and reported by others [17,27], suggesting appropriate patient selection is the key to success. Traditionally in adult practice when open repair was performed for MH, both thoracotomy and laparotomy had produced equal results [6,50].…”
Section: Accepted Manuscriptmentioning
confidence: 53%
“…Our systematic review selected publications dated back to 1997, as MIS repair of MH was first reported by Georgacopulo et al that year [10]. MIS continues to be utilised for its advantages in recovery time, length of stay, and analgesia requirement compared to the open approach and more importantly laparoscopy in experienced centres produced less complication and equally good results [13,17]. Effective laparoscopic primary repair has been made possible with the development of various modifications with use of Endo Stitch (Covidien) for intracorporeal suturing [26], or application of extracorporeal knot-tying techniques with knots buried in the subcutaneous layer [25].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Disease usually occurs in children, where statistics exceed 20 observations and chromosome abnormalities (15%). In 75% of cases, a congenital abnormality such as Down (5,6). Malformations are rarely found in adults (7).…”
Section: Discussionmentioning
confidence: 99%
“…The signs, also in the case of children, are respiratory (56.5%), gastrointestinal (19%), or combined (6.8%); The diagnosis is determined by chest x-ray, ultrasound, CT (6). Diagnosis can also be performed prenatally.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital Morgagni hernia is clinically unique as compared with other CDH, and chance appearance of an unknown mass on chest radiography for other conditions is possible, similar to that in the present case. 3,5 Ultrasonography is useful for detecting diaphragmatic defects in the neonatal period and early infancy.…”
mentioning
confidence: 99%